2014
DOI: 10.2298/ciceq121127029s
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of transglutaminase and L-ascorbic acid on substandard quality wheat flour by response surface methodology

Abstract: Article Highlights• Dough and bread quality of substandard flour can be improved by using TG and L-AA • RSM was applied in the analysis of the individual and interactive effect of TG and L-AA • TG has more linear effect in the fermentation process, on the crumb quality than L-AA • L-AA has a much greater effect on the specific volume of bread than TG • Desirability function defines optimum dose of TG and L-AA for sample of flour substandard quality AbstractOver the past decade, extreme variations in climatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The 0.04 U/g of flour Amy586 supplemented dough had a less significant effect. Various studies (Kaya & Sahin, ; Simurina et al, ) reported that the W value for standard quality wheat ranges from 160 to 200 × 10 −4 J. This result further demonstrated the positive effect of Amy586 supplementation, improving rheological dough properties.…”
Section: Resultsmentioning
confidence: 63%
“…The 0.04 U/g of flour Amy586 supplemented dough had a less significant effect. Various studies (Kaya & Sahin, ; Simurina et al, ) reported that the W value for standard quality wheat ranges from 160 to 200 × 10 −4 J. This result further demonstrated the positive effect of Amy586 supplementation, improving rheological dough properties.…”
Section: Resultsmentioning
confidence: 63%
“…Due to its positive effects on dough properties, ascorbic acid (AsA) has been used as a flour improver for a long time. Ascorbic acid is a very popular and widely used flour improver in bread products to incentives oxidizing process (Joye, Lagrain & Delcour, 2009;Šimurina et al, 2014). The addition of ascorbic acid (AsA) has a well-studied strengthening effect on dough that leads to a higher rising of the dough (Koehler, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is typically used in doses of 50-70 mg/kg flour (Wieser, 2003), but wider ranges of 10-200 mg/kg are also proposed (Selomulyo & Zhou, 2007;Šimurina, Filipčev, Jovanov, Ikonić & Simović-Šoronja, 2013). Nevertheless, as for most dough con-ditioners, its effect is not only dose-dependent but dependent on the initial quality of flour and the type of bread-making method (Pečivová, Pavlínek & Hrabê, 2011;Šimurina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…L-Ascorbic acid (L-AA), one of the most widely used flour improvers, increases dough strength and improves bread volume and crumb structure (4). The L-AA enhances the rheological properties of dough is primarily via its electron-donating capacity and the formation of reactive products such as O 2 − (5).…”
Section: Introductionmentioning
confidence: 99%
“…Xylanase hydrolyzes arabinoxylans that interfere with the formation of a gluten network (10). Combinations of chemical oxidizing agents and crosslinking enzymes have frequently been used to improve the quality of flour and the end product (4,(11)(12)(13). Simurina et al investigated the effect of a combination of TGase and L-AA on substandard quality wheat flour and observed an improvement in dough properties as well as the quality of bread prepared from substandard wheat flour compared to dough and bread without these additives.…”
Section: Introductionmentioning
confidence: 99%